Religion and equality: law in conflict - Durham, W. Cole; Thayer, Donlu (ICLARS series on law and religion, 2016)
Conscience and equality : negotiating emerging tensions / Russell Sandberg -- The right to religion : considerations of the principal International and European juridical instruments / Nicolae V. Dur -- Freedom of religion : Strasbourg and Luxembourg compared / Mark Hill QC -- State neutrality, religion, and the workplace in the recent case law of the European Court of Human Rights / María J. Valero Estarellas -- Religious freedom, anti-discrimination, and minority rights in Brazil / Rodrigo Vitorino Souza Alves -- Anti-discrimination legislation and regulation of employment decisions of religious schools in Australia / Greg Walsh -- Same-sex marriage : exemptions for celebrants and religious freedom / Rex Ahdar -- Marriages, civil unions, partnerships, and religion in South Africa after 1996 / Pieter Coertzen -- A fissure within the human rights system? : same-sex marriage claims and religious freedom of speech / Ursula C. Basset -- A 'Bare . . . purpose to harm'? Marriage and Catholic conscience / Helen M. Alvaré -- Protecting same-sex marriage and religious liberty / Thomas C. Berg and Douglas Laycock -- Religion and equality : reconcilable differences? / W. Cole Durham, Jr